The relationship between lower-limb strength and match-related muscle damage in elite level professional European soccer players - Owen, A.; Dunlop, G.; Rouissi, M.; Chtara, M.; Paul, D.; Zouhal, H.; Wong, D. P. (Journal of Sports Sciences, 2015)
In professional soccer, the benefits of lower limb strength training have been advocated. However, from an aspect of performance development, specifically with respect to expression of fatigue and injury prevention, the advantages of increased lower body strength have received limited attention at the elite level of the game. The primary aim of this cross-sectional investigation was to examine the association between lower body strength and the expression of markers of fatigue as evaluated through muscle damage assessment following match play in professional soccer players. Ten male professional soccer players participated in this investigation (mean ± SD age 26.2 ± 4.3 years, height 181.6 ± 4.8 cm and body mass 78.7 ± 6.1 kg); creatine kinase (CK) was collected 2-days post-match for a 5-month period and at three different time points (Phase 1, Phase 2 and Phase 3); muscular strength (e.g. 4 repetition half-squat) was measured 3-day post-match. No significant change in CK and muscular force across three time points was found (F = 0.60, P = 0.56, ny2 = 0.06 and F = 2.65, P = 0.10, ny2 = 0.23, respectively). Muscular force was negatively correlated (moderate to very large) with CK. It can be concluded that players who produce greater lower body force as a result of being stronger in the lower limbs show reduced levels of CK 48 h post-match.